Are Suspects Who Resist Arrest Defiant, Desperate, or Disoriented?. (July 2016) - Whichard, Corey; Felson, Richard B.
Objectives: We examine three reasons why suspects resist arrest: (1) defiance of police authority by suspects from lower-status groups, (2) risky decisions resulting from aversion to sure losses, and (3) impairment due to mental illness and substance use. Methods: We use nationally representative survey data from about 17, 000 state and federal inmates who were asked whether they resisted arrest when they committed the crime that led to their incarceration. Results: Suspects' resistance is unrelated to their race/ethnicity, education, or unemployment. On the other hand, suspects are more resistant when they are carrying contraband (e.g., illegal weapons, drugs, stolen property) or are under community supervision (i.e., parolees, probationers, or escapees). Resistance is also positively related to mental illness, illicit drug use, and alcohol intoxication. Conclusions: Our results do not support the idea that resistance is an expression of defiance from lower-status suspects. They are consistent with prospect theory, which argues that decision makers become risk-seeking, when the alternative is to accept a sure loss. Our results suggest that resistant suspects are best understood as either desperate or disoriented decision makers.